Experimental evaluation of a constructive system for earthquake resisting masonry enclosure walls - Silva, Luís (2016)
University of Minho is a partner of the INSYSME research project (Innovative Systems for earthquake resistant masonry enclosures in RC buildings), funded by the European Commission. The main aims of this project are to study new systems for masonry infill walls, which combine simplicity with low cost, and to propose recommendations and calculation procedures for their design to seismic actions, filling an existing gap in current regulations. At University of Minho a new construction system for masonry enclosures was developed, being composed of a new commercial unit and vertical steel reinforcement placed in ceramic brick frogs, connected to top and bottom beams. In this paper, the experimental work developed at the University of Minho for validation of the solution proposed for masonry infills is presented and discussed. The experimental validation process of the solution for the masonry enclosure walls was based on in-plane and out-of-plane static cyclic tests. The tests were carried in four specimens built at reduced scale (1:1.5). In order to assess the in-plane behaviour, two specimens have been tested. The first test was done, in a specimen with masonry infill, until maximum drift. In the second test, only reinforcement concrete frame was tested, to access the contribution of masonry infill. For out-of-plane direction two specimens were tested one without reinforcement, and other with reinforcement. The out-of-plane test was carried using an airbag system. In this case only positive direction was considered. In-plane and out-of-plane tests were performed under displacement control according to a load pattern defined based on the FEMA 461 recommendations.